Fast on-site screening of 3, 4-methylenedioxyethylamphetamine (MDEA) in forensic samples using carbon screen-printed electrode and square wave voltammetry. (20th January 2022) - Novais, Augusto dos Santos; Arantes, Luciano Chaves; Almeida, Eduardo Santos; Rocha, Raquel Gomes; Lima, Camila Diana; Melo, Larissa Magalhães de Almeida; Richter, Eduardo Mathias; Munoz, Rodrigo Alejandro Abarza; Pio dos Santos, Wallans Torres; da Silva, Rodrigo Amorim Bezerra
Abstract: The worldwide seizures of illicit synthetic drugs have been dramatically increasing over the past decade, when the quantity of seized amphetamine-type stimulants (ATS) quadrupled, while seized ecstasy (3, 4–methylenedioxymethamphetamine or MDMA)-like substances doubled. In this work, a simple and fast methodology for the electrochemical screening of ecstasy analogue MDEA (3, 4-methylenedioxyethylamphetamine) in forensic samples is presented, for the first time, using a carbon screen-printed electrode (C-SPE) and square wave voltammetry (SWV). The electrochemical behavior of MDEA was studied by cyclic voltammetry at different pH values (2 to 12), where an altered electrochemistry of this drug on C-SPE, with an unreported redox pair, was observed in comparison with previous works dealing with the voltammetric detection of other ATS with similar chemical structures. Based on the acquired electrochemical processes, a redox reaction mechanism for MDEA on C-SPE is proposed. The best conditions (sensitivity and selectivity) for MDEA screening were obtained by SWV (a: 40 mV, f : 30 Hz, and Estep : 4 mV) and 0.04 mol L −1 Britton Robinson buffer solution at pH 3.0 as the supporting electrolyte. The proposed method presents a wide linear range (2.5 to 30.0 µmol L −1, R 2  > 0.99), high sensitivity (0.569 µA / µmol L −1 ), low theoretical limit of detection (0.03 µmol L −1 ), and good repeatability using the same C-SPE (RSD < 6%; n  = 10). The inter-device reproducibility ( n  = 5) showed a minimal variation of peak potentials (RSD < 2.3%). The interference study was performed with some adulterants usually found in ecstasy tablets, such as paracetamol, caffeine, glucose, ketamine, cocaine, acetylsalicylic acid, amphetamine (A), methamphetamine (MA), 3, 4-methylenedioxyamphetamine (MDA), MDMA, ethylone (bk-MDEA), n-ethylpentylone (bk-EBDP) and dibutylone (bk-DMDBD). The method was applied in real seized samples containing MDEA with addition-recovery studies close to 100%. The developed method is promising to be used as a preliminary test for the screening of MDEA in the ever-changing situation concerning seized forensic samples. The proposed sensor exhibits attractive features for application in forensic analysis, such as rapidness, simplicity, low-cost, user friendly and portability. Graphical abstract: Image, graphical abstract